Sero-prevalence of Johne's disease in prospective young bulls of Hariana breed by indigenous ELISA kit, using protoplasmic antigen from 'Bison type' genotype of Mycobacterium avium subspecies paratuberculosis of goat origin - Singh, S V; Singh, A V; Shukla, N; Singh, P K; Sohal, J S; Gupta, V K; Vihan, V S (The Indian Journal of Animal Sciences, 2007)
Johne's disease, caused by Mycobacterium avium subspecies paratuberculosis, is in the list B of OIE and requires certification of atleast breeding animals. Presently, India lacks diagnostic kits and reagents against Johne's disease. ELISA kit initially developed for screening of goats and sheep has been adapted to screen cattle. Prospective young bulls of best native milch breeds of cows (Hariana), belonging to farmers' herds were screened against Johne's disease (JD) by indigenous ELISA kit using protoplasmic antigen from novel 'Bison type' genotype of Map of goat origin. Young males to be used as breeding bulls and aged between 2.5 and 3.5 years were earmarked for purchase from Rohtak district of Hariana. Of the 23 bulls, none was strong positive, 20 (86.9%) were positive and 3 (13.0%) were low positive. However, none were suspected and negative. The sero-prevalence was 86.9% in young bulls of Hariana breed, in their native tract. In another study, Mycobacterium avium subspecies paratuberculosis was isolated from all the 5 categories of S/.P ratio in goats. Therefore, real prevalence of JD in bulls of Hariana breed may be still higher. High sero-prevalence of JD in the native tract of best Indian milch breed of cows is due to poor attention and low priority given to Johne's disease surveillance and control in the country.